Analisis Sosiologi Sastra Novel Anak Bakumpai Terakhir Karya Yuni Nurmalia - Khairi, Fathul (Humanis; Volume 16. No. 3. September 2016)
Object of this research is a novel titled Anak Bakumpai Terakhir by Yuni Nurmalia. Problems discussed in this research are structures and social aspects of Dayak in Anak Bakumpai Terakhir. The structures of Anak Bakumpai Terakhir, include : theme, plot, characters, and setting. The theme of Anak Bakumpai Terakhir is enviromental damage issues and also the existency of Dayak Bakumpai that is being endangered. The plot of Anak Bakumpai Terakhir is a progressive plot. The characters in this novel is divided into main character and additional characters. The main character is Aruna and the additional characters are Kai, Dayu, Samudera, Eliyana, dan Avara. The setting of place of Anak Bakumpai Terakhir  is taken in Kalimantan, the setting of time is about in 20th century, and the setting of social told about the society life of Dayak Bakumpai . Social aspects of Dayak Bakumpai in Anak Bakumpai Terakhir include economical aspect, value aspect, society aspect, educational aspect, and cultural aspect. Economical aspect uncover prosperity issues in Dayak Bakumpai. Value aspect discuss the right and wrong value issues. Society aspect discuss the relationship issue between the main character and family, society, and other individu. Educational aspect cover two things: formal and informal education. Cultural aspect discuss the custom and tradition in Dayak Bakumpai society.
Keywords: novel, sociological literature, and Daya